2005
DOI: 10.1677/joe.1.05607
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 71 kDa protein as a putative non-genomic membrane progesterone receptor in boar spermatozoa

Abstract: A putative non-genomic progesterone receptor was identified by Western blot analysis from the membrane fraction but not the cytosolic fraction of boar spermatozoa using monoclonal antibody (mAb) C-262. When the membrane and the cytosolic fractions of boar liver, kidney, uterus and spermatozoa were analyzed with mAb C-262, protein bands with molecular masses of 86 and 120 kDa were detected from the cytosolic fraction of the uterus, whereas a 71 kDa protein was detected from the membrane fraction of spermatozoa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…It also stimulates ZP penetration and the AR in hamster spermatozoa (Libersky & Boatman 1995b, Llanos & Anabalon 1996. Although spermatozoa do not have a classic intracellular progesterone receptor (PGR), a PGR is present in the cell membrane (Sabeur et al 1996, Baldi et al 1998, 2009, Lösel & Wehling 2003, Luconi et al 2004, Jang & Yi 2005. Moreover, it has been suggested that progesterone binds to the acrosome region, and PGR is localized to the same region in human (Gadkar et al 2002) and hamster spermatozoa (Noguchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulates ZP penetration and the AR in hamster spermatozoa (Libersky & Boatman 1995b, Llanos & Anabalon 1996. Although spermatozoa do not have a classic intracellular progesterone receptor (PGR), a PGR is present in the cell membrane (Sabeur et al 1996, Baldi et al 1998, 2009, Lösel & Wehling 2003, Luconi et al 2004, Jang & Yi 2005. Moreover, it has been suggested that progesterone binds to the acrosome region, and PGR is localized to the same region in human (Gadkar et al 2002) and hamster spermatozoa (Noguchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane receptors are involved with the regulation of mammalian sperm function (Shen et al 1993;Roldan et al 1994;Allegrucci et al 2001;Adeoya-Osiguwa and Fraser 2005;Jang and Yi 2005). Some membrane receptors are functionally coupled to G-proteins which can alter intracellular cAMP and calcium concentrations (Eason et al 1992;Pihlavisto and Scheinin 1999;Pohjanoksa et al 1997;Allegrucci et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ni and co-workers reported that progesterone regulates CRH gene transcription via a cAMP regulatory element in the CRH promoter (Ni et al, 2004). Recently, the human membrane progesterone receptor (Jang and Yi, 2005) and receptor gene were identified (Bernauer et al, 2001). Hanna and co-workers also suggested that zebrafish membrane progestin receptor (mPR) alpha and mPR beta signal similarly upon progestin binding, resulting in rapid activation of MAPK and downregulation of adenylyl cyclase activity (Hanna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%